1999
DOI: 10.1021/jf980452j
|View full text |Cite
|
Sign up to set email alerts
|

Similarities in the Aroma Chemistry of Gewürztraminer Variety Wines and Lychee (Litchi chinesisSonn.) Fruit

Abstract: GC/O analysis of canned lychees indicated that cis-rose oxide, linalool, ethyl isohexanoate, geraniol, furaneol, vanillin, (E)-2-nonenal, beta-damascenone, isovaleric acid, and (E)-furan linalool oxide were the most odor potent compounds detected in the fruit extracts. However, on the basis of calculated odor activity values (OAVs), cis-rose oxide, beta-damascenone, linalool, furaneol, ethyl isobutyrate, (E)-2-nonenal, ethyl isohexanoate, geraniol, and delta-decalactone were determined to be the main contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
124
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(135 citation statements)
references
References 12 publications
8
124
1
2
Order By: Relevance
“…The results obtained show that farnesol, linalool and ␣-terpineol are markedly the most abundant monoterpenols in Boal, Malvasia, Sercial and Verdelho musts, but these compounds are present at levels lower than their perception threshold [19][20][21]. Farnesol is the main monoterpenol present in the Boal must variety.…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained show that farnesol, linalool and ␣-terpineol are markedly the most abundant monoterpenols in Boal, Malvasia, Sercial and Verdelho musts, but these compounds are present at levels lower than their perception threshold [19][20][21]. Farnesol is the main monoterpenol present in the Boal must variety.…”
Section: Resultsmentioning
confidence: 99%
“…Correlations between floral sensory attributes and high levels of free linalool and α-terpineol in these varieties have been well documented (Williams et al 1981, Günata et al 1985, Wilson et al 1986, De La Presa-Owens and Noble 1997, Lee and Noble 2003, 2006, Campo et al 2005. In addition, (Z)-rose oxide has been identified as an important impact aroma compound in Gewürztraminer wines (Guth 1997a) and is associated with the lychee aroma attribute common to this variety (Ong and Acree 1999). Finally, the monoterpene "wine lactone" is an important aroma component in Gewürztraminer wines (Guth 1997a(Guth , 1997b).…”
Section: Terpenesmentioning
confidence: 95%
“…One of the more important compounds in these studies, furaneol, was first identified in wines by Rapp and colleagues (Rapp et al 1980) and has been identified in Vitis hybrid varieties (e.g., Baco and Villard noir), V. lambrusca varieties (e.g., Noah and Isabella), and V. vinifera varieites (e.g., Carignan and Gewürztraminer) Bertrand 1995, Ong andAcree 1999). A recent study of Italian V. vinifera varieties (Genovese et al 2005) has also suggested that furaneol is important to the aroma of Refosco and Primitivo (also known as Zinfandel in the United States and Crljenak kaštelanski or Pribidrag in Croatia; Maletić et al 2004).…”
Section: Furan Derivatives and Furanonesmentioning
confidence: 99%
“…Identification of hydrolyzed components was carried out by: (i) comparing the GC retention times and mass spectra, with those, when available, of the pure standard compounds, (ii) all mass spectra were also compared with the data system library (NIST, 2005 software, Mass Spectral Search Program V.2.0d; NIST 2005, Washington, DC), and (iii) retention index probes (RI) value were determined according to the van den Dool and Kratz [33]. For the RI determination, a C 8 -C 20 n-alkanes series were used, and these values were compared, when available, with values reported in the literature for a BP-20 and similar chromatographic columns [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52].…”
Section: Gc-qms Conditionsmentioning
confidence: 99%